Impact of the COVID-19 Pandemic on Korean Adolescents' Mental Health and Lifestyle Factors - Lee, Jongha; Ko, Young-Hoon; Chi, Suhyuk; Lee, Moon-Soo; Yoon, Ho-Kyoung (Journal of Adolescent Health, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused changes in the daily lives of Korean adolescents and affected their emotional well-being. This study compared lifestyle factors and the mental health status of adolescents before and during the COVID-19 pandemic. We conducted a secondary analysis using data from a national cross-sectional cohort (Korean Youth Risk Behavior Web-based Survey, KYRBS) collected in 2019 before the COVID-19 outbreak and in 2020 during the pandemic. This study included 57,303 students from the 2019 KYRBS and 54,948 from the 2020 KYRBS. Lifestyle factors such as dietary habits, physical activity levels, time spent studying, duration of Internet use, and mental health status, including perceived stress, experience of depressive mood, and suicidal ideation and attempts, were included in the analyses. The perceived stress levels, self-reported depressive mood, and suicidal thoughts and attempts were lower in the students surveyed in 2020 during the COVID-19 pandemic than in the students surveyed in 2019 before the COVID-19 outbreak. The time spent studying and sleep duration decreased compared to before the pandemic, and sleep satisfaction increased during the COVID-19 pandemic. Our results showed an improvement in mental health status in Korean adolescents during the pandemic, but caution is needed when interpreting these results. Future research is needed to determine the effects of a long-lasting pandemic on mental health and lifestyle factors in adolescents.